Microstructural Characterization and Mechanical Properties Investigation of Nemalloy HE700 alloy: Effect of Pre-Solidified Grains. Issue 1 (1st January 2023) - Aziz, T.; Sadayappan, K.; Phillion, A.; Shankar, S.
Abstract: Structural plate castings of Nemalloy HE700 alloy, an Al-Fe eutectic alloy system with Zn and Mg as precipitation strengtheners were produced through high vacuum high pressure die casting (HVHPDC) and designed as an alternative to existing structural automotive materials. Cast materials are subject to the existence of pre-solidified grains (PSG) within the microstructure that originate from external solidification in the liquid melt and cause defects in the final cast components. In the case of HPDC, these PSG emerge in the shot sleeve and are injected through the gating system, influencing liquid metal flow behaviour and solidification characteristics. The extent of PSG and their distribution were manipulated through the altering of process route parameters such as shot delay intervals. Quantitative metallography and the effect of PSGs on the uniaxial tensile properties for the Nemalloy HE700 alloy are presented in this publication.